Grouped SPME Comparison of Floral Scent as a Method of Unlocking Phylogenetic Patterns in Volatiles - Latinovic, Adelina; Nichols, David S.; Adams, Vanessa M.; McQuillan, Peter B. (Frontiers in Ecology and Evolution, 2022)
The global rate of crop production has exceeded the availability of pollination services provided by managed honeybees and habitat loss remains a key factor in the loss of wild pollinators. Revegetation of agricultural land and wild pollination may provide a solution, however collection of floral trait data that correlates to pollinator preferences remains an under-studied and complex process. The Tasmanian Midlands constitute a region where 83% of the original vegetation has been cleared and crop pollination demand for the carrot seed industry cannot be met by managed pollination services. We report the floral profiles of 15 unstudied native Australian plant species and the extent to which they match the commonly cultivated seed crops of Daucus carota L and Brassica rapa L. Through solid-phase microextraction (SPME) paired with gas chromatography–mass spectrometry (GC-MS), we identify a set of inter-family shared, common floral volatiles from these plant species as well as unique and characteristic patterns. The approach detailed in this study, involving scent analysis, ordination (NMDS) and clustering outputs provides a fast and reproducible method for broadly grouping flora based on scent and may be harnessed to facilitate better decision-making processes for future revegetation projects. Based on this approach, we propose that planned, landscape-scale reintroduction of native flora that is tailored to crop pollination can provide both an agricultural and ecological benefit.